Risiko Produksi pada Usahatani Kelapa (Cocos Nucifera) di Kecamatan Teluk Pakedai - Arviana, Sagita; Dolorosa, Eva; Suharyani, Anita (Universitas Galuh, 2025)
This study aims to understand the level of production risk faced by coconut farmers and the factors influencing production risk in coconut farming in Teluk Pakedai District. Therefore, this study takes a sample of 67 farmers. The research employs both qualitative and quantitative approaches. The qualitative analysis is used to describe and explain the conditions and phenomena occurring in the study, while the quantitative analysis is used as a tool to analyze the factors affecting production using the Just and Pope model. Additionally, the level of production risk faced by coconut farmers is identified using the Coefficient of Variation (CV).The results of the analysis show that the production risk level of coconut farmers in Teluk Pakedai District is relatively low, with a coefficient of variation (CV) value of 0.46, indicating that coconut production is relatively stable. Furthermore, the variables of land area, farmer’s age, farming experience, number of family dependents, and seedlings do not have a significant effect on coconut production. However, labor has a significant influence on the production risk of coconut farming in Teluk Pakedai District.